Landasan Dan Fungsi Al-Qawa’id Al-Fiqhiyyah Dalam Problematika Hukum Islam - Abdul Muiz (al-Afkar, Journal For Islamic Studies, 2020)
Jurisprudence or al-qawaid al-fiqhiyyah did not exist in the time of the Prophet Muhammad. Jurisprudence comes later after fiqh and usul fiqh. The foundation of the formulation of fiqh rules comes from the texts of the Koran, Sunnah, Ijma ', and Qiyas. There are differences in al-qawaid al-fiqhiyyah different from al-qawaid al-ushuliyyah, namely al-qawaid al-fiqhiyyah is the majority rule that can be applied to most of its branches. Meanwhile, qawaid ushuliyyah is a means to issue amaliy sharia law. There is no standard number of all the principles of fiqh, but the scholars classify all of them into five main rules, namely 1) al-age bi maqashidiha, 2) al-yaqinu la yuzalu bi al-syakk, 3) al-masyaqqatu tajlinu al- taisir, 4) al-dhararu yuzalu, 5) al-'adatu muhakkamatun. Of the five rules, all have branches that are not counted exactly. The function of fiqh rules is to be a tool for mujtahid, judge, imam, and mufti. This is because the problems of life in society are increasingly complex, and also not all problems have a direct answer whether it's in the Koran, Sunnah, Ijma 'or Qiyas. Therefore, the principle of fiqh has an important function as part of the methods and instruments in the formulation of Islamic law.